Acute Toxicity by Oral Co-Exposure to Palytoxin and Okadaic Acid in Mice - Silvio Sosa; Marco Pelin; Cristina Ponti; Michela Carlin; Aurelia Tubaro (Marine Drugs, 2022)
The frequent occurrence of marine dinoflagellates producing palytoxin (PLTX) or okadaic acid (OA) raises concern for the possible co-presence of these toxins in seafood, leading to additive or synergistic adverse effects in consumers. Thus, the acute oral toxicity of PLTX and OA association was evaluated in mice: groups of eight female CD-1 mice were administered by gavage with combined doses of PLTX (30, 90 or 270 μg/kg) and OA (370 μg/kg), or with each individual toxin, recording signs up to 24 h (five mice) and 14 days (three mice). Lethal effects occurred only after PLTX (90 or 270 μg/kg) exposure, alone or combined with OA, also during the 14-day recovery. PLTX induced scratching, piloerection, abdominal swelling, muscle spasms, paralysis and dyspnea, which increased in frequency or duration when co-administered with OA. The latter induced only diarrhea. At 24 h, PLTX (90 or 270 μg/kg) and OA caused wall redness in the small intestine or pale fluid accumulation in its lumen, respectively. These effects co-occurred in mice co-exposed to PLTX (90 or 270 μg/kg) and OA, and were associated with slight ulcers and inflammation at forestomach. PLTX (270 μg/kg alone or 90 μg/kg associated with OA) also decreased the liver/body weight ratio, reducing hepatocyte glycogen (270 μg/kg, alone or combined with OA). No alterations were recorded in surviving mice after 14 days. Overall, the study suggests additive effects of PLTX and OA that should be considered for their risk assessment as seafood contaminants.